The acute radiation syndrome—need for updated medical guidelines. (25th January 2022) - Stenke, Leif; Hedman, Christel; Lagergren Lindberg, Marita; Lindberg, Karin; Valentin, Jack
Abstract: The major immediate and severe medical consequences in man following exposure to high doses of ionising radiation can be summarised within the concept of the acute radiation syndrome (ARS). In a dose-dependent fashion, a multitude of organ systems can be affected by such irradiation, presenting considerable medical challenges to treating physicians. Accidents or malevolent events leading to ARS can provoke devastating effects, but they occur at a low frequency and in a highly varying manner and magnitude. Thus, it is difficult to make precise medical predictions and planning, or to draw conclusive evidence from occurred events. Therefore, knowledge from on-going continuous developments within related medical areas needs to be acknowledged and incorporated into the ARS setting, enabling the creation of evidence-based guidelines. In 2011 the World Health Organization published a first global consensus on the medical management of ARS among patients subjected to nontherapeutic radiation. During the recent decade the understanding of and capability to counteract organ damage related to radiation and other agents have improved considerably. Furthermore, legal and logistic hurdles in the process of formally approving appropriate medical countermeasures have been reduced. We believe the time is now ripe for developing an update of internationally consented medical guidelines on ARS.